11-2(d-1)=(-2d)+13

Simple and best practice solution for 11-2(d-1)=(-2d)+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11-2(d-1)=(-2d)+13 equation:


Simplifying
11 + -2(d + -1) = (-2d) + 13

Reorder the terms:
11 + -2(-1 + d) = (-2d) + 13
11 + (-1 * -2 + d * -2) = (-2d) + 13
11 + (2 + -2d) = (-2d) + 13

Combine like terms: 11 + 2 = 13
13 + -2d = (-2d) + 13

Reorder the terms:
13 + -2d = 13 + (-2d)

Add '-13' to each side of the equation.
13 + -13 + -2d = 13 + -13 + (-2d)

Combine like terms: 13 + -13 = 0
0 + -2d = 13 + -13 + (-2d)
-2d = 13 + -13 + (-2d)

Combine like terms: 13 + -13 = 0
-2d = 0 + (-2d)
-2d = (-2d)

Add '2d' to each side of the equation.
-2d + 2d = (-2d) + 2d

Combine like terms: -2d + 2d = 0
0 = (-2d) + 2d

Combine like terms: (-2d) + 2d = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 4(3+x)=x | | 11-2(d-1)=(-2d)+13w | | 3(3x+7)-10=-277 | | 2=2(k+3)-10 | | x^2+2kx+k^2-3k+6=0 | | 2.25(4x-4)=-2t+10x+12 | | 3+k/3=3 | | 2(s+2)=6 | | 3.5=130+10x | | (-4)(p+8)=12 | | 150m-100m+39000=40000-150m | | 22+2z=37+6*z | | 12w-19w-1=13 | | w(w-13)=0 | | -x+2(4-x)=-4 | | Sin(x)=-1 | | 6y=-120 | | 6x=32 | | 16=p-(-3) | | 10m+8b-12=0 | | -15+7x=-79 | | (x+3)+(y-5)=36 | | -25(d+2)= | | 14x+9y=310 | | 16.4(2x+11)=6x+33 | | 2990=4*660+6y | | 12x+9y=310 | | -2(z-9)=-24 | | y-10=-2(x+2) | | 7u-6u+2=20 | | 2990=4*650+6y | | .5x-9=.2x |

Equations solver categories